Peningkatkan Kinerja Guru Melalui Penerapan Gaya Kepemimpinan Kepala Sekolah di MA Majma’ul Bahroin Desa Tapos II Tenjolaya - Kartika, Ika; Siti Masitho; Sri Yanih; Tri Sumarsih; Ramdhani, Deni (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
Increasing the success of teacher performance is largely determined by the leadership style of a school principal in his capacity as a leader. This research aims to obtain data results regarding: (1). Increasing teacher work discipline through the leadership style of the school principal. (2). The principal through his leadership style is able to increase teacher work motivation. (3). Increased teacher responsibility through the leadership style of the school principal. (4). In improving teacher performance, there are obstacles or constraints faced by school principals. This approach uses a qualitative approach through descriptive methods. With data collection techniques using observation, interviews and documentation studies. From the results of this research it can be concluded that: (1). In order to improve discipline, an instructive leadership style (telling) is applied by the school principal. (2). In increasing teacher work motivation, a consultative (selling) leadership style is applied by the school principal. (3). In increasing teacher responsibility, the school principal applies a delegative leadership style. (4) In learning, there are obstacles or obstacles faced by school principals, namely, decreased teacher discipline, reduced teacher work motivation, and low teacher responsibility in learning. There are suggestions from the author so that the desired goals can be achieved well and maximally, a good leadership style can be applied that is optimally suited to the situation and conditions by the school principal.